The Cross-Cultural Legacy of Lin Yutang : Critical Perspectives - Qian, Suoqiao (China research monographs, 2015)
"Lin Yutang (18951976) was the modern Chinese writer and intellectual best known to the Western world in the twentieth century. Hailed as a Chinese philosopher, Lin was the de facto spokesman for China and Chinese culture and played the role of cultural ambassador between China and the United States. This critical volume, representing the best international scholarship on Lin Yutang studies to date, is a first attempt at a comprehensive study on the cross-cultural legacy of Lins literary practices in and across China and America. The essays collected here, most of which were first presented at the international conference on the cross-cultural legacy of Lin Yutang in China and America held at the City University of Hong Kong in December 2011, offer different perspectives on Lins cross-cultural legacy."